The boy who was raised by librarians - Morris, Carla D.; Sneed, Brad. (Atlanta, GA : Peachtree, 2007)
Melvin discovers that the public library is the place where he can find just about anything--including three librarians who help in his quest for knowledge.
Accelerated Reader AR
Keywords: Librarians -- Juvenile fiction; Libraries -- Juvenile fiction